Interpretive Structural Modeling of Tobacco Farmer Institutions: Pathways to Strengthen Economic Resilience and Welfare in Bojonegoro, Indonesia - Durroh, Badiatud; Sriyatun, Sriyatun; Masahid, Masahid (Universitas Negeri Gorontalo, 2025)
The plantation sub-sector plays a strategic role in Indonesia’s economy, with tobacco being one of the most important and competitive commodities contributing to regional income and employment. Bojonegoro Regency is recognized as one of the main tobacco production centers in Indonesia, yet its farmer institutions remain weak and fragmented. This study addresses the gap in understanding the structural relationships among institutional actors involved in tobacco farming. The objective was to analyze the hierarchical structure and interaction patterns of these actors to strengthen institutional performance and sustainability. The Interpretive Structural Modeling (ISM) method was applied using data collected from experts and key stakeholders in Bojonegoro’s tobacco farming sector. The ISM results revealed that tobacco farmers, PT. AOI, and the Agricultural Service possess the highest driving power and occupy the Independent sector, acting as the main driving forces of institutional development. Meanwhile, Farmer Groups and Suppliers have the lowest driving power, categorized as Dependent actors, indicating their heavy reliance on institutional and policy support. These findings highlight that improving institutional sustainability requires strengthening collaboration between independent and dependent actors, while optimizing the coordinating role of linkage actors such as the Regional Government and Agricultural Extension Workers. Overall, the study provides practical insights for policymakers to design targeted interventions that enhance the effectiveness and resilience of tobacco farmer institutions in Bojonegoro Regency.